Trust in Virtual Teams: A Systematic Review of Information Systems Literature - Watanuki, Hugo Martinelli; Moraes, Renato de Oliveira (Journal of Information Systems and Technology Management, 2022)
The issue of trust development amongst members of virtual teams is gaining increasing attention from Information Systems (IS) scholars due to the advancement of virtual collaboration in organizations. The objective of this study is to evaluate the issue of trust development in virtual team research from the perspective of main IS journals, and to consolidate the contributions made by IS researchers. To this aim, a systematic review of the literature has been conducted, supported by bibliometric and Social Network Analysis (SNA). An IS-centric review of trust concepts and research paradigms has been presented along with opportunities for future research.